Efficacy of local anaesthetic solutions on the success of inferior alveolar nerve block in patients with irreversible pulpitis: a systematic review and network meta‐analysis of randomized clinical trials. (12th February 2019) - Nagendrababu, V.; Pulikkotil, S. J.; Suresh, A.; Veettil, S. K.; Bhatia, S.; Setzer, F. C.
Abstract: The management of pain during root canal treatment is important. The aim of this systematic review and network meta‐analysis was to identify the anaesthetic solution that would provide the best pulpal anaesthesia for inferior alveolar nerve blocks (IANB) treating mandibular teeth with irreversible pulpitis. Two electronic databases (PubMed and Scopus) were searched to identify studies up to October 2018. Randomized clinical trials comparing at least two anaesthetic solutions (lidocaine (lignocaine), articaine, bupivacaine, prilocaine or mepivacaine) used for IANB for treatment of irreversible pulpitis were included. The revised Cochrane risk of bias tool for randomized trials was used to assess the quality of the included studies. Pairwise meta‐analysis, network meta‐analysis using a random‐effects model, and SUCRA ranking were performed. The network meta‐analysis estimated the probability of each treatment performing best. The quality of evidence was assessed using the Grading of Recommendations, Assessment, Development and Evaluations approach. In total, 11 studies ( n  = 750) were included in the meta‐analysis. The network meta‐analysis revealed that only mepivacaine significantly increased the success rate of IANB compared to lidocaine (RR, 1.42 [95% CI 1.04–1.95]). However, no significant differences in the success rate of IANB were observed between mepivacaine and other anaesthetic agents (articaine and bupivacaine). Of all anaesthetic agents, mepivacaine (SUCRA = 0.81) ranked first in increasing the success rate of IANB, followed by prilocaine (SUCRA = 0.62), articaine (SUCRA = 0.54), bupivacaine (SUCRA = 0.41) and lidocaine (SUCRA = 0.13). The overall quality of evidence was very low to moderate. In conclusion, based on the evidence from the randomized clinical trials included in this review, mepivacaine with epinephrine demonstrated the highest probability of providing effective pulpal anaesthesia using IANB for teeth with irreversible pulpitis compared to prilocaine, articaine, bupivacaine and lidocaine. Further, high‐quality clinical trials are needed to support the conclusion of this review.